Identification of promising types of shrubs suitable for introduction in Astana, Kazakhstan - A. Shaldybayeva; D. Sarsekova; S. Mukhtubayeva (Caspian Journal of Environmental Sciences)
In the course of the study, a comparative analysis was carried out on the various types of shrubs that may be potentially interesting for introduction in Astana, Kazakhstan. Their phenological and botanical features, such as height, shape of the bush, colour and size of flowers, seasonal flowering and decorative foliage, were studied. Special attention was paid to the adaptation of these species to local conditions, such as climate, soil and water availability. Observations of their growth and development over several years were carried out to determine their stability and suitability for acclimatization in an urban environment. The possibility of using these types of shrubs in the landscape design of Astana was also evaluated. The issues of combining them with other plants, creating compositions and also aesthetically attractive plant ensembles were considered. The results of the study allowed us to identify the most promising local types of shrubs suitable for introduction in Astana, as well as to highlight recommendations for their use in landscaping the city. The obtained data and conclusions will be useful for specialists involved in the planning and creation of public and private spaces, as well as for local governments. Thus, this study will be a comprehensive analysis and the introduction of promising local species of shrubs in Astana, taking into account their suitability for local conditions and the possibility of use in the landscape design of the city.